If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7/3)y=42
We move all terms to the left:
(7/3)y-(42)=0
Domain of the equation: 3)y!=0We add all the numbers together, and all the variables
y!=0/1
y!=0
y∈R
(+7/3)y-42=0
We multiply parentheses
7y^2-42=0
a = 7; b = 0; c = -42;
Δ = b2-4ac
Δ = 02-4·7·(-42)
Δ = 1176
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1176}=\sqrt{196*6}=\sqrt{196}*\sqrt{6}=14\sqrt{6}$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-14\sqrt{6}}{2*7}=\frac{0-14\sqrt{6}}{14} =-\frac{14\sqrt{6}}{14} =-\sqrt{6} $$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+14\sqrt{6}}{2*7}=\frac{0+14\sqrt{6}}{14} =\frac{14\sqrt{6}}{14} =\sqrt{6} $
| 0.2x+63=0.2x+53 | | -7u-13=-4(u-2) | | -0,5(x-4)-7,3=0,8(2-x) | | 5x+2x+3x=-70 | | 11n-5n-3n-2n=7 | | -5(1+x)+x=-3(6+2x)+6 | | 3(2x+1)=3(x+4 | | 1=v/4 | | -1|3z=8/3 | | 2x-5x=-14-7 | | 9x-58=18” | | -9a+-6a+5a+2a=16 | | 15v=8v+14 | | 20=20+z | | 9n-1n+18=n-1n+26 | | 5.3x-1.7=19.5 | | 3n-14=-7(-3n+2)+3n | | 52+r=126 | | -60=-2x-8x | | 14=v+4 | | 14w-2w-w+4w-13w=12 | | g2+2g=7 | | 2p/3-7=17 | | 5+11*2=c | | 2(5x-2)=14-8x | | -3=40x-8 | | 8(m+8)=80 | | 3x+3x+5x+5x=126 | | 5(u+7)-8u=17 | | 6r-2r-3r-r+4r=4 | | 2^(2*x)-(21)=0 | | 34x-40=75 |